STRATEGI PELAYANAN PRIMA TERHADAP KEPUASAN PELANGGAN DI PUSKESMAS ARJUNO - Yessiska Stefanni Lafrense; Cakra Yusron Syahputra; Arisandi Nurin Syafitri (Juremi: Jurnal Riset Ekonomi, 2024)
Excellent service strategy used at Arjuno Community Health Center to increase customer satisfaction. The excellent service strategies implemented include improving service information systems, increasing service quality, developing service delivery, improving service facilities and tools, and increasing customer satisfaction. By implementing these strategies, the Arjuno Community Health Center guarantees optimal health and quality of service for the community. The aim of this research is to improve the service information system and improve service quality. The method used is literature and qualitative study